Implementasi Program Kampus Mengajar Angkatan 5 Dalam Meningkatkan Kemampuan Literasi Dan Numerasi Di SMP Nasional Surabaya - Ni Luh Ayu Atmi Kamaratih; Cholis Hidayati (Universitas Kristen Indonesia Toraja, 2023)
Teaching Campus – Merdeka Campus (MBKM) is a program from the Ministry of Education and Culture that empowers Indonesian students to be able to contribute directly for one semester in the world of education, especially in developing literacy and numeracy skills as well as technology adaptation. Students who pass the selection in this program are assigned to school partners selected by the organizers of the Teaching Campus program. One of the schools targeted by this program is the Surabaya National Middle School. The method used in this research is descriptive qualitative with data collection in the form of interviews, observation and documentation. Implementation of the Teaching Campus Program at the National Middle School is going well. This is reviewed based on aspects of program suitability with targets, programs with executors, and executors with appropriate targets. Students get a lot of hands-on experience in the field, both during learning and also when compiling programs with colleagues. Meanwhile, the placement school admits that the presence of students has helped a lot, both in the field of teaching programs and assisting with technology adaptation.